2014
DOI: 10.1152/physiolgenomics.00120.2013
|View full text |Cite
|
Sign up to set email alerts
|

Liver functional genomics in beef cows on grazing systems: novel genes and pathways revealed

Abstract: Laporta J, Rosa GJM, Naya H, Carriquiry M. Liver functional genomics in beef cows on grazing systems: novel genes and pathways revealed. Physiol Genomics 46: 138 -147, 2014. First published December 10, 2013; doi:10.1152/physiolgenomics.00120.2013.-The adaptation of the liver to periods of negative energy balance is largely unknown in beef cattle on grazing systems. We evaluated liver transcriptome throughout gestation and early lactation of purebred and crossbred beef cows [Angus, Hereford, and their F1 cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…A microarray study of the effect of pregnancy and diet in liver gene expression revealed specific hepatic adaptations of beef cows to different nutritional environments. For example, the study found clear evidence of gluconeogenesis in the liver of pregnant cows during limited forage availability ( Laporta et al, 2014 ). Using candidate gene approach or transcriptomics investigating genomic peripartal adaptions in dairy cows provided insights into physiological function and genetics of key tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A microarray study of the effect of pregnancy and diet in liver gene expression revealed specific hepatic adaptations of beef cows to different nutritional environments. For example, the study found clear evidence of gluconeogenesis in the liver of pregnant cows during limited forage availability ( Laporta et al, 2014 ). Using candidate gene approach or transcriptomics investigating genomic peripartal adaptions in dairy cows provided insights into physiological function and genetics of key tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the liver has multiple other physiological functions in the body including immune response, regulating inflammation and the removal of xenobiotics [ 11 , 12 ]. A previous gene array study on beef cows demonstrated marked hepatic responses to high or low grazing herbage allowances of native grasslands, including genes associated with glucogenesis, fatty acid oxidation, cell growth, DNA replication and transcription [ 13 ]. The proteomic profile of hepatic tissue in goats fed a high-grain diet demonstrated that an altered expression of hepatic proteins was related to amino acids metabolism [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before use, primer product size (as estimated by 1% agarose gel separation) and sequence (Macrogen Inc., Seoul, Korea) were determined to ensure that primers produced the desired amplicons (data not shown). The genes selected for this study were selected based on previous results from a microarray analysis (Laporta et al, 2014). Mitochondrial respiratory complex candidate genes selected were: NADH:ubiquinone oxidoreductase subunit C1 (NDUFC1, complex I); NADH:ubiquinone oxidoreductase subunit A4 (NDUFA4, complex I); NADH:ubiquinone oxidoreductase subunit A13 (NDUFA13, complex I); succinate dehydrogenase complex, subunit A, flavoprotein (Fp) (SDHA, complex II); succinate dehydrogenase complex, subunit D (SDHD, complex II); ubiquinol-cytochrome c reductase core protein I (UQCRC1, complex III); ubiquinol-cytochrome c reductase hinge protein (UQCRH, complex III); cytochrome c oxidase assembly factor (COX19, complex IV); cytochrome c-1 (CYC1, complex IV); ATP synthase, H + transporting, mitochondrial F1 complex, epsilon subunit (ATP5E, complex V); ATP synthase, H+ transporting, mitochondrial F1 complex, O subunit (ATP5O, complex V); and citrate synthase (CS).…”
Section: Quantitative Real-time Qpcrmentioning
confidence: 99%